THE DIFFERENCE EFFECTIVENESS OF SHUTTLE RUN COMBINATION WITH ZIG ZAG RUN IN NEURAL MOBILIZATION INTERVENTION TO IMPROVE AGILITY IN SOCCER PLAYERS IN MEDICAL FACULTY UDAYANA UNIVERSITY - Dharma, I Made Hardi Wira; Andayani, Ni Luh Nopi; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 3 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i03.p09, 2018)
ABSTRACT   The purpose of this study is to know difference effectiveness of shuttle run combination with zig zag run in neural mobilization intervention to improve agility in soccer players. This research is an experimental study of Pre and Post Test Two Group Design. It is consist of 20 people was divided into 2 groups used simple random sampling technique, with students of medical faculty udayana university for the sample. Analysis data for normality used Saphiro wilk and homogeneity used  Levene’s test , hypothesis test used paired sample t-test and independent t-test. The research showed group 1 was normal and homogen distribution, there was an average decreasing time of 3.92 seconds (21.07%) with p = 0,000 (p <0.05 ), While in Group 2 was tested with Paired Sample T-test because of normal and homogen data, there was an average decrease of 4.72 seconds (24.25%) with p = 0,000 (p <0.05). The result showed there is improvement agility in each group. The difference between group 1 and 2 was obtained p = 0,001 (p <0.05) that’s mean there are significant difference in increase of agility before and after intervention. The conclusion of this study is zig zag run and neural mobilization training is more effectively used to improve agility in football players at the Faculty of Medicine Udayana University.   Keywords : Agility, shuttle run, zig zag run, neural mobilization